A Comprehensive Review of Dietetic Regimen (Pathya- Apathya) in Skin Disorders (International Journal of Ayurveda and Pharma Research, 2024)
For decades, it was thought that there was no relation between the dermatological conditions or the skin disorders and the diet. But recent studies have made an attempt to explore the relationship between the diet and its role in skin disorders. Ayurvedic system of Medicine also known as the Indian traditional medicine has contributed vastly for the diet and the management of skin disorders. In Ayurveda skin disorders are explained under the name Kustha which are twenty in number and two types as Mahakustha and Kshudra kustha. Since 5000yrs, Ayurveda is serving the society with the objective of curing of the disease and prevention of the same. Ahara has been given the prime importance in Ayurveda and is placed one among the Trayopasthambas or the three pillars of life such as Aaahara (diet), Nidra (sleep) and Brahmacharya (celibacy) In depth of diet for the healthy and also the specific diet for the disorders has been described in Ayurveda and is being practiced by Ayurvedic practitioners since centuries which is witnessed in the latest research studies. The present study has made an attempt to assess both the Modern and Ayurvedic concepts of diet that is presently practiced and their importance in the management of skin disorders.